Structural dynamics and transient lipid binding of synaptobrevin-2 tune SNARE assembly and membrane fusion - Lakomek, Nils-Alexander (Proc Natl Acad Sci U S A, 2019)
Intrinsically disordered proteins (IDPs) and their conformational transitions play an important role in neurotransmitter release at the neuronal synapse. Here, the SNARE proteins are essential by forming the SNARE complex that drives vesicular membrane fusion. While it is widely accepted that the SNARE proteins are intrinsically disordered in their monomeric prefusion form, important mechanistic aspects of this prefusion conformation and its lipid interactions, before forming the SNARE complex, are not fully understood at the molecular level and remain controversial. Here, by a combination of NMR and fluorescence spectroscopy methods, we find that vesicular synaptobrevin-2 (syb-2) in its monomeric prefusion conformation shows high flexibility, characteristic for an IDP, but also a high dynamic range and increasing rigidity from the N to C terminus. The gradual increase in rigidity correlates with an increase in lipid binding affinity from the N to C terminus. It could also explain the increased rate for C-terminal SNARE zippering, known to be faster than N-terminal SNARE zippering. Also, the syb-2 SNARE motif and, in particular, the linker domain show transient and weak membrane binding, characterized by a high off-rate and low (millimolar) affinity. The transient membrane binding of syb-2 may compensate for the repulsive forces between the two membranes and/or the SNARE motifs and the membranes, helping to destabilize the hydrophilic-hydrophobic boundary in the bilayer. Therefore, we propose that optimum flexibility and membrane binding of syb-2 regulate SNARE assembly and minimize repulsive forces during membrane fusion.